2001
DOI: 10.1046/j.1464-410x.2001.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐institutional analysis of laparoscopic orchidopexy

Abstract: Objective To combine and analyse the results from centres with a large experience of laparoscopy for the impalpable testis with small series, to determine the expected success rate for laparoscopic orchidopexy. Methods A questionnaire was distributed to participating paediatric urologists; each contributor retrospectively reviewed the clinical charts for their cases of therapeutic laparoscopy for an impalpable testis, detailing 36 variables for each patient. The data were collated centrally into a computerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(93 citation statements)
references
References 27 publications
6
83
0
4
Order By: Relevance
“…To date, the only other published multicenter study (10 sites, n = 281 patients) reported overall 7.2% and 6.1% rates of failure and atrophy, respectively, in patients undergoing laparoscopic orchidopexy. 21 We found that at least two-thirds of corrective surgeries for UDT were 5 Values are expressed as n (%). a Some simultaneous orchidopexy and orchiectomy.…”
Section: Discussionmentioning
confidence: 93%
“…To date, the only other published multicenter study (10 sites, n = 281 patients) reported overall 7.2% and 6.1% rates of failure and atrophy, respectively, in patients undergoing laparoscopic orchidopexy. 21 We found that at least two-thirds of corrective surgeries for UDT were 5 Values are expressed as n (%). a Some simultaneous orchidopexy and orchiectomy.…”
Section: Discussionmentioning
confidence: 93%
“…One should be aware of the inferior results of the laparoscopic primary orchiopexy with vascular ligature (primary or one stage Fowler-Stephens). In the literature (20), the reported success was 74.1%. In our series, with the exception of a few cases, we only reached 33% of well located and normal testes.…”
Section: Commentsmentioning
confidence: 97%
“…50 The laparoscopic FS orchidopexy entails division of the gonadal vessels and cremasteric collaterals during advancement of the IAT medial to the inferior epigastric vessels or obliterated umbilical artery. Despite its widespread use, [51][52][53][54] either as a one-or two-stage procedure, atrophy rates can be as high as 33%, probably due to failure of developing adequate collateral blood supply through the deferential artery. The presence of a long looping vas deferens may increase this risk, especially when the procedure is done laparoscopically.…”
Section: Fowler-stephens Orchidopexymentioning
confidence: 99%